Probabilistic modelling of tool unbalance during cutting of hard-heterogeneous materials: A case study in Ceramic Matrix Composites (CMCs). (1st September 2018) - Diaz, O. Gavalda; Axinte, D.A.; Novovic, D.
Abstract: Compared to other materials, CMCs display a unique high hardness and heterogeneous nature which are critically reflected during the drilling process where asymmetrical high forces are suffered by the tool, resulting in an unbalance of the drill bit. Hence, this study proposes a mechanistic approach where the hard nature resulting in high radial forces is analytically studied and coupled with a probabilistic model where the heterogeneous nature of CMCs is taken into consideration. This theoretical study results in an in-depth understanding of the loading unbalance occurring on different tool sizes during drilling of CMCs which can lead to a premature tool breakage. The nature of this unique force that is assumed in the theoretical approach to influence the cutting of hard-heterogeneous materials is experimentally validated by drilling a homogeneous and a heterogeneous hard ceramics, i.e. a monolithic SiC and a SiC/SiC CMC. Moreover, the model developed together the with drilling experiments with different tool diameters result in an understanding of why small tool diameters suffer a premature tool breakage when drilling difficult-to-machine CMCs. Highlights: A radial force appearing when drilling hard-heterogeneous materials (CMCs) has been reported for the first time. The stochasticity created by the heterogeneous nature of CMCs has been modelled and simulated. A mechanical approach allowing the calculation of the stress that a tool suffer when drilling CMCs is proposed. Experimental trials with different drill diameters for a CMC and a homogenous ceramic have been presented.